1961
DOI: 10.1021/ac60179a030
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Indicator Adsorption Analysis of Gasoline on Partially Deactivated Silica Gel Columns

Abstract: Investigation of the accuracy of fluorescent indicator adsorption analysis, using certain blends of known olefin content, showed per cent olefins observed to be consistently low. The use of silica gel containing 4% of its weight of water reduces the error to within the stated limits of repeatability of the method. Examination of cuts taken from columns using standard dry silica gel showed tailing of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1964
1964
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The combination of these driving forces with the different operating modes of FFF (normal FFF, steric FFF, hyperlayer FFF, etc.) provides a very large and diverse collection of subtechniques for application to particulate and macromolecular separation problems (3,4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of these driving forces with the different operating modes of FFF (normal FFF, steric FFF, hyperlayer FFF, etc.) provides a very large and diverse collection of subtechniques for application to particulate and macromolecular separation problems (3,4).…”
Section: Resultsmentioning
confidence: 99%
“…The fluorescence indicator adsorption (FIA) method, ASTM D 1319 (1), has been used for many years by the petroleum industry to determine saturates, olefins, and aromatic hydrocarbons in petroleum products. This method suffers from many problems (2,3), including the following; (a) poor precision due to the operator's inability to distinguish the borders of the colored bands, (b) long analysis time, (c) poor resolution between the hydrocarbon groups, (d) limited applicability to colored samples (i.e., higher-molecular-weight samples), (e) limited applicability to samples containing pentane or lighter hydrocarbons, and (f) lot-to-lot variations in dye composition.…”
mentioning
confidence: 99%
“…Improvement of the FIA procedure along the lines suggested by Norris, Shively, and Constantin (11) for gasoline analysis was studied. Four per cent by weight of water was added to the FIA adsorbent, and the nine samples were reanalyzed.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have been reported on modification of the silica gel (4)(5)(6), the dyes (7), and the mobile phase (8) in an attempt to improve the precision of the method. In an effort to reduce the human error introduced by visually selecting the start of each colored zone, attempts have been made to instrumentalize the method by using HPLC (9,10) and GC (11) for hydrocarbon type analysis.…”
mentioning
confidence: 99%